Percutaneous pulmonary valve implantation – state of the art and Polish experience - Biernacka, Elżbieta K.; Rużyłło, Witold; Demkow, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Percutaneous pulmonary valve implantation (PPVI) is a relatively new method of treating patients with right ventricular outflow tract (RVOT) dysfunction after surgical repair of congenital heart disease. Since its introduction in 2000 by Bonhoeffer, more than ten thousand PPVI procedures have been performed worldwide. Indications for PPVI have been adapted from those accepted for surgical intervention. Two types of valves are being used: Melody Medtronic available in diameters 16 mm and 18 mm and the family of Edwards SAPIEN valves 23, 26 and 29. The procedure has been shown to be feasible and safe when performed in patients with full pulmonary conduit dysfunction and in selected cases of patched RVOT. The low complication rate and the reduced number of open-chest re-interventions over a patient’s lifetime are among the main advantages of the procedure. The most important problem responsible for late mortality and reinterventions is infective endocarditis. Size restrictions of the currently available valves limit deployment in the majority of patients with a wide RVOT. Newer devices are being developed to make these patients suitable for PPVI. A literature review, Polish experience and results of PPVI performed in 66 patients in the Institute of Cardiology in Warsaw are briefly reported.